Impression Management and Career Related Outcomes: A Systematic Literature Review - Al-Shatti, Esraa; Ohana, Marc (Frontiers in Psychology, 2021)
Despite the popularity of the term impression management (IM) in the literature, there is no consensus as how different types of IM (direct vs indirect) and modes of interaction (face-to-face vs online) promote career-related outcomes. While most empirical studies focus on direct IM, individuals engage in both types of IM and interaction modes, particularly indirect IM in the online context. Indeed, recent developments suggest that online interactions now prevail over face-to-face interactions, especially during the COVID-19 pandemic. Accordingly, this study presents the first systematic literature review that differentiates between types of IM (direct vs indirect) and modes of interaction (face-to-face vs online) in a career development perspective. The review shows that direct IM is more widely studied in the face-to-face than online interaction mode, while indirect IM is neglected in both interaction modes. This study thus provides evidence of the need to investigate and differentiate between the different types of IM and interaction modes for career-related outcomes, highlighting some research gaps and directions for future inquiry.